The effect of redials and retrials on the GSM Network - Gyamfuaa, Mintah Jennifer (2013)
A thesis submitted to the Department of Electrical and Electronic Engineering, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the award of Master of Science degree, November-2012